Fractional CO2 Laser in Treatment of Surgical and Trumatic Scars - Khudhair Khalaf Al-Kayalli; Shahad Khudhair Khalaf; Mohammad Husain Motllag (Diyala Journal of Medicine, 2019)
Background: Scars result from chronic wound healing response , leaving behind fibrotic tissue due to irregular collagen formation . There are different types of scar including atrophic , hypertrophic, contracture and keloid scars. Available scar revision therapies depend on the type of scar , and range from topical creams for mild scarring , to grafting in the case of large , traumatic scars . Laser scar revision is an effective method for treating a wide rang of scars that improves skin texture and pigment as well as functional aspects .